INFLUENCES OF FAMILY AND HOUSEHOLD CHARACTERISTICS ON CHILDREN'S LEVEL OF PHYSICAL ACTIVITY DURING SOCIAL DISTANCING DUE TO COVID-19 IN BRAZIL - Cristhina Bonilha Huster Siegle; André Pombo; Carlos Luz; Luis Paulo Rodrigues; Rita Cordovil; Cristina dos Santos Cardoso de Sá (Sociedade de Pediatria de São Paulo, 2020)
ABSTRACT Objective: To evaluate if the variables child's sex, age, presence of siblings, parents working remotely, and external space affect the level of physical activity (PA) of Brazilian children during social distancing imposed by the COVID-19 pandemic. Methods: An online questionnaire was applied by the LimeSurvey software from March to April 2020. Children were divided into four age groups, and the questionnaire comprised questions on family and household characteristics, domestic and children's routines in the period of Brazilian social distancing. Based on the answers concerning children's activities, the following variable was created: percentage of physical activity (%PA) in one-day period. Analysis of variance and regression analysis were performed to investigate the effect of demographic and parental activities on %PA. Results: The %PA decreases with increasing age, but increases with the availability of external space at home. No significant or interaction effects were observed for other variables. Age and external space at home are predictors of %PA. Conclusions: Household and personal characteristics of Brazilian children influence the level of physical activity performed by them during social distancing. Preventive measures can be adopted in the face of another similar period.